Substrate adhesion of rat hepatocytes: a comparison of laminin and fibronectin as attachment proteins (The Rockefeller University Press, 1981)
In previous studies rat hepatocytes have been shown to adhere to substrates composed of collagen or fibronectin. In the present communication, the basement membrane protein laminin is reported to mediated the attachment and spreading of hepatocytes. The cell attachment-mediating activity of laminin was compared with that of fibronectin. The activity of fibronectin was heat sensitive, whereas laminin retained its activity after boiling. On the other hand, reduction and alkylation or periodate oxidation of the proteins affected only the cell attachment activity of laminin. Preincubation of cells with soluble fibronectin inhibited initial cell attachment to fibronectin but not to laminin substrates, and, reversely, soluble laminin selectively inhibited cell attachment to laminin. These results suggest that attachment of cells to substrates of the two proteins involves different cellular receptors recognizing distinct and nonidentical structures in the proteins.